University digital media co-occurrence networks reveal structure and dynamics of brand visibility in the attention economy - Alexander Michael Petersen (Humanities & Social Sciences Communications)
Abstract As universities compete for visibility to attract student enrollment and build scientific reputation, the management of institution of higher education (IHE) brand has emerged as an important strategic endeavor. Yet our understanding of the factors that condition the structure and dynamics of brand stratification within regional IHE ecosystems is limited. Instead, our best approximation for brand equity derives from widespread IHE rankings, which lack contextual and relational features for understanding the patterns of engagement in the fast-moving attention economy, and in particular how institutional partnerships can generate brand equity by leveraging ecosystem network effects. To this end, here we develop a framework for measuring two dimensions of brand equity, namely visibility, and association, according to the frequency of digital media articles featuring a university’s official name. We demonstrate this approach for 29 universities in California and Texas based upon 2 million media articles published between 2000 and 2020 and validate our approach by correlating university digital media visibility with ARWU Shanghai rankings and freshman enrollment growth. As roughly 10% of the article sample features >1 university, longitudinal analysis of institutional co-occurrence reveals the extent to which brand association stratifies according to regional proximity, institutional specialization, and prestige. Interestingly, despite the shared value generated from media co-visibility, the frequency of multi-university media articles has declined over time, which we attribute to paradigm shifts in media content production following the 2007–08 financial crisis and the COVID-19 infodemic, in addition to increased competitiveness of the attention economy. Topic classification of media article titles shows how specialized institutions may strategically manage their brand equity by aligning content production with dominant media topics to reinforce brand visibility with broader social, technological, and environmental narratives.